2009
DOI: 10.1387/ijdb.082681ms
|View full text |Cite
|
Sign up to set email alerts
|

Ceratitis capitata transformer-2 gene is required to establish and maintain the autoregulation of Cctra, the master gene for female sex determination

Abstract: In Drosophila melanogaster, transformer-2 (TRA-2) which is a non-sex-specific auxiliary splicing factor, is required to promote female sexual differentiation by interaction with the female-specific TRA. The two proteins positively regulate the splicing of both doublesex (dsx) and fruitless (fru) pre-mRNAs, which in turn regulate phenotypic and behavioural sexual dimorphism. In the Mediterranean fruitfly Ceratitis capitata, the female-specific CcTRA is similarly required not only for Ccdsx splicing, but also to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
237
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(270 citation statements)
references
References 52 publications
(53 reference statements)
18
237
1
6
Order By: Relevance
“…fru is a gene with highly pleiotropic functions, some of which are essential for viability in both sexes (Anand et al, 2001;Song et al, 2002;Song and Taylor, 2003). Previous studies have suggested that fru should be evolutionarily conserved (Wilkins, 1995;Gailey et al, 2006;Salvemini et al, 2009;Clynen et al, 2011), yet it has also been implicated in the production of sexually dimorphic behaviour, which is known to change rapidly between species (Mendelson and Shaw, 2005;Kraaijeveld et al, 2011). In addition, fru has also been implicated as a potential candidate gene for the production of species-specific behaviour differences (Gleason and Ritchie, 2004;Sobrinho and de Brito, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fru is a gene with highly pleiotropic functions, some of which are essential for viability in both sexes (Anand et al, 2001;Song et al, 2002;Song and Taylor, 2003). Previous studies have suggested that fru should be evolutionarily conserved (Wilkins, 1995;Gailey et al, 2006;Salvemini et al, 2009;Clynen et al, 2011), yet it has also been implicated in the production of sexually dimorphic behaviour, which is known to change rapidly between species (Mendelson and Shaw, 2005;Kraaijeveld et al, 2011). In addition, fru has also been implicated as a potential candidate gene for the production of species-specific behaviour differences (Gleason and Ritchie, 2004;Sobrinho and de Brito, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions occurring within alternatively spliced genes are both more localised (mainly in those exons being alternatively spliced) and less conservative than those in genes that have been duplicated (Talavera et al, 2007). The gene fruitless (fru) is an alternatively spliced transcription factor that has been identified in a broad range of insect groups (Salvemini et al, 2010), including Orthoptera (Ustinova and Mayer, 2006;Boerjan et al, 2011), Blattodea (Clynen et al, 2011), Hymenoptera (Bertossa et al, 2009) and Diptera (Ryner et al, 1996;Gailey et al, 2006;Salvemini et al, 2009;Sobrinho and de Brito, 2010;Salvemini et al, 2013). fru is a pleiotropic gene with at least two major functions: one that controls male sexual behaviour and another that is essential for viability in both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is reminiscent of that in Ceratitis, where Salvemini and co-workers (Salvemini et al 2009) recently reported that Cctra2 is required to maintain the productive female-specific splicing mode of Cctra. The presence of multiple clusters of putative TRA/TRA2 binding sites, intronic splice silencers (ISS), and RBP1 binding sites in the sex-specifically processed region suggested that CcTRA and CcTRA2 form a complex that directly associates with Cctra pre-mRNA to impose the female splice (Salvemini et al 2009). Clustering of such putative binding sites was also previously observed in tra orthologs of other tephritids (Ruiz et al 2007).…”
mentioning
confidence: 84%
“…In F 1 /F 1 females, on the other hand, transient silencing of Mdtra2 causes a complete and irreversible shift to male development, indicating that Mdtra2 is required for upholding the self-sustaining feedback loop of F (Burghardt et al 2005). This situation is reminiscent of that in Ceratitis, where Salvemini and co-workers (Salvemini et al 2009) recently reported that Cctra2 is required to maintain the productive female-specific splicing mode of Cctra. The presence of multiple clusters of putative TRA/TRA2 binding sites, intronic splice silencers (ISS), and RBP1 binding sites in the sex-specifically processed region suggested that CcTRA and CcTRA2 form a complex that directly associates with Cctra pre-mRNA to impose the female splice (Salvemini et al 2009).…”
mentioning
confidence: 95%
“…Anastrepha suspensa (SACCONE et al, 2007;SALVEMINI et al, 2009;SARNO et al, 2010;LIU et al, 2015), sua utilização é bastante improvável. Isso por que a técnica de injeção de dsRNA diretamente nos embriões desses tefritídeos além de consistir em uma metodologia trabalhosa resulta em uma altíssima mortalidade ao procedimento:…”
Section: -Introduçãounclassified